Optimalisasi Fungsi dan Peran Manajemen Keperawatan pada Level Kepala Ruang dalam Pendokumentasian Supervisi Berbasis IT - Eva Oktaviarini; Krisna Yetti; Ade Suhendri; Muhammad Hadi (Journal of Telenursing (JOTING), 2023)
This research aims to optimize the role of the head of the room in implementing supervision with IT-based documentation at the Khidmat Sehat Afiat Hospital, Depok, which can then improve the performance of nurses which will influence the goals and vision of the hospital. This research method uses a case study approach with interviews, document review and observation, as well as carrying out problem analysis using fishbone analysis. The research results showed that when identifying the need to improve the implementation of tiered nurse supervision related to electronic-based documentation, improving supervision guidelines, SPO assessment formats, preparing schedules, socializing and testing electronic-based supervision instruments that had to be developed during the implementation phase. The evaluation phase requires support with monitoring and evaluation. Conclusion. This innovation in IT-based monitoring documentation received a positive response and was enthusiastically accepted by all management management levels in the hospital. So as to facilitate the implementation of supervision and can improve the quality of service. Keywords: IT-Based Documentation, Service Quality, Clinical Supervision